(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Aim: to study and to compare the sagittal and vertical changes of the upper incisors and first premolars resulting from molar distalization using both appliances (2k-loop) and (pendulum) separately. Materials and Methods: This study was designed as a two-arm prospective clinical trial and the study sample included 16 patients with dental bilateral Class II molar relationship equally divided into two groups eight per group and changes were evaluated using lateral cephalometric radiographs of the head. Results: we found that a mesial tipping occurred with a mesial move of the maxillary first premolars by (3.38°, 2.64mm) respectively For the (2k-loop) appliance group, and by(3.37°, 2.61mm) For the (pendulum) appliance group, we also obtained a vestibular inclination with a mesial move of the upper incisors by an amount of (4.03°, 2.26mm) respectively For the (2k-loop) appliance group, and by (4°, 2,62mm) For the (pendulum) appliance group and the difference was not statistically significant between the two appliances in the sagittal plane, In the vertical plane, there were extrusion in the maxillary first premolars in (2k-loop) group and (pendulum) group by an amount of (2.01mm, 2.43 mm) respectively, and the difference was not statistically significant for the therapeutic changes in the vertical plane between the two appliances. Conclusions: The study concluded that the traditional method of anchoring using the Nance button supported to the bands of the maxillary first premolars in both appliance (2k-loop) and (pendulum) was unable to achieve the required anchorage. And that there is no difference in the anchoring control between the two appliances.